Hormonal Contraception and Violent Death: The Physiological and Psychological Links - Lanfranchi, Angela (Frontiers in Behavioral Neuroscience, 2021)
In the past decade, two large prospective cohort studies of British and American women have been conducted which found a statistically significant increase in the risk of violent death in ever-users of hormonal contraceptives. Research on the effects of hormonal contraceptives upon the behaviors of intimate partners and on the physiology of women using hormonal contraceptives has provided insight into the possible basis for the resulting increase in violent death. This review examines the changes that are potential contributors to the reported increase.